Children terminally aill: family reaction to assistence given and the difficulties felt by the nurse of the pediatric ward - Horta, Ana Lúcia de Moraes; Araújo, Ana Paula de Campos; Aprile, Carla Metello; Echalar, Constanza Machado; Paredes, Fátima Neves; Caminada, Sirlene (Revista da Escola de Enfermagem da USP, 1989)
This study reported family's reaction of the child terminally ill, identified by the pediatric nurses. It focuses on the suggested assistance to the family and on the pediatric nurses difficulties in this situation. This study was carried out with 35 nurses working at two University Hospitals. We based the analysis on the phases of dying of KUBLER-ROSS and Guide of Communication with parents of WHALEY & WONG, besides our own categorization.